The Impact of Lifestyle on the Destination Choice - A Field Study on Jordanian Tourist - Elham Tomalieh (My University, 2013)
This study aims to examine the impact of lifestyle on the Jordanian tourist attitude toward a vacation, and a destination choice. The study tested five hypotheses on the independent variable (Lifestyle: work, hobbies, family and interests) and their impact on the dependant variables: Attitude toward a vacation and the destination choice. The study findings addressed the importance of Jordanian tourists’ lifestyle on formulating their attitude toward a vacation and on their destination choice. The study concluded that the Jordanian tourist prefers to visit the destinations which are suitable for families, followed by the shopping areas, and then natural and historical places. The results indicate that there are no differences in Jordanian tourists’ attitude toward a vacation, and on their destination choice, due to demographic factors, such as (sex, or age, or income, or occupation, or education).

سعت الدراسة إلى اختبار أثر نمط حياة السائح الأردني في موقفه من الإجازة، وفي اختياره لموقع الإجازة. تم اختبار خمس فرضيات تناولت المتغير المستقل (نمط الحياة: العمل، والهوايات، والعائلة، والاهتمامات) وتأثيرها في المتغيرات التابعة وهي: الموقف من الإجازة، واختيار موقع الإجازة. وتوصلت الدراسة إلى أن هناك تأثيراً لنمط حياة السائح في موقفه من الإجازة، وفي اختياره لموقع الإجازة. وأن السائح الأردني يفضل أولا زيارة مواقع الراحة العائلية، ثم أماكن التسوق، ويلي ذلك الأماكن الطبيعية والتاريخية. وخلصت الدراسة الى أنه لا توجد فروق في موقف السائح الأردني من الإجازة أو اختيار موقعها، تعزى لأي من خصائصه الديموغرافية (الجنس أو العمر أو الدخل أو الوظيفة أو مستوى التعليم).
أثر نمط الحياة في اختيار مواقع الإجازة - دراسة ميدانية للسائح الأردني